Numerical prediction based on XFEM for mixed-mode crack growth path and fatigue life under cyclic overload - Chen, Zhiying; Bao, Hongchen; Dai, Yanwei; Liu, Yinghua (International journal of fatigue, 2022)
•An efficient and stable method for crack growth is proposed based on XFEM.•The SIFs of mixed-mode crack is accurately calculated.•Crack paths of structures with complex configuration are accurately predicted.•The shell-to-solid model of large engineering structure is simulated.•The different cyclic overload effects on fatigue life are analyzed systematically. The numerical prediction based on the extended finite element method (XFEM) is carried out in this paper, where the mixed-mode crack propagation process is simulated accurately and the fatigue life considering the cyclic overload effect is calculated conveniently by using the proposed novel method. In this method, a simple crack surface updating strategy that can simulate the through-thickness crack in a three-dimensional structure is proposed, and it replaces the complex level set updating algorithm. Meanwhile, the cycle-by-cycle method for overload fatigue life is also proposed. The prediction is implemented based on the ABAQUS software by Python codes and the corresponding functional modules are developed. Compared with the built-in crack propagation modules of XFEM in ABAQUS, the method in this paper contains the complete crack tip enhancement functions and presents strong robustness in computational convergence and excellent calculation efficiency. The accuracy in calculating stress intensity factors (SIFs) and predicting mixed-mode crack growth paths is verified through examples. In addition, the fatigue life under cyclic overload is also predicted accurately by the developed modules. The effects from different parameters of load spectrum with overload are obtained according to the numerical results. Moreover, combined with the shell-to-solid coupling method, the large and complex practical engineering structure is simulated and analyzed in detail.